The double-edged sword of keeping livestock: Balancing nutritional benefits with disease risks in poor nations - Zerfu, Taddese Alemu (Cambridge University Press, 2023)
In many low- and lower-middle-income countries, particularly in Sub-Saharan Africa (SSA), where mixed crop-livestock farming is widely practiced, livestock keeping provides income, food, nutrition and other benefits for the rural poor. The nutritional benefits of livestock keeping are particularly important since malnutrition continues to cause nearly half of annual global child deaths, and can have lasting effects on the physical growth and cognitive development of millions of surviving children. However, the relationship between livestock keeping, human nutrition and the health of most vulnerable population groups—under-five children and women of reproductive age—has remained a complex problem in many LMICs. This problem prompted us to work together and synthesize global evidence to assess the role of livestock keeping on the health and nutritional status of children and women in LMICs.